2016
DOI: 10.1007/s10096-016-2703-z
|View full text |Cite
|
Sign up to set email alerts
|

Nosocomial pneumonia in 27 ICUs in Europe: perspectives from the EU-VAP/CAP study

Abstract: We report on intensive care nosocomial pneumonia (NP) in Europe through a review of EU-VAP/CAP manuscripts: a prospective observational study, enrolling patients from 27 ICUs in nine European countries. From 2,436 eligible ICU patients, 827 cases presented NP, with 18.3 episodes of VAP per 1000 ventilator-days. Most common findings were worsening oxygenation, purulent respiratory secretions and temperature increase. At least three criteria from Clinical Pulmonary Infection score (CPIS) were present in 77.9 % o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
229
4
23

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 288 publications
(270 citation statements)
references
References 37 publications
14
229
4
23
Order By: Relevance
“…The recent article published by Koulenti et al [63] on data from 27 ICUs in Europe from the EU-VAP/CAP study analyzed 2436 patients. Among NP cases, HAP occurred in 20.6%, VAP in 42.7% and very early-onset VAP (VE-VAP) in 12.7% of cases.…”
Section: Microbial Etiology Of Hospital Acquired Pneumonia (Hap)mentioning
confidence: 99%
See 1 more Smart Citation
“…The recent article published by Koulenti et al [63] on data from 27 ICUs in Europe from the EU-VAP/CAP study analyzed 2436 patients. Among NP cases, HAP occurred in 20.6%, VAP in 42.7% and very early-onset VAP (VE-VAP) in 12.7% of cases.…”
Section: Microbial Etiology Of Hospital Acquired Pneumonia (Hap)mentioning
confidence: 99%
“…Pneumonia caused by more than two pathogenic microorganism is defined as polymicrobial and approximately 30%–70% of VAP cases are considered to have polymicrobial origen [63,68,69]. The study by Combes et al [69] found no differences regarding epidemiology data or clinical outcomes between monomicrobial cases or polymicrobial cases.…”
Section: Microbial Etiology Of Hospital Acquired Pneumonia (Hap)mentioning
confidence: 99%
“…The most common gram-positive bacteria are methicillin-resistant Staphylococcus aureus (MRSA) and vancomycin-intermediate S. aureus. The most common gram-negative bacteria are Pseudomonas aeruginosa, Acinetobacter species, and Enterobacteriaceae which may be either extended-spectrum βlactamase (ESBL)-producing or carbapenem-resistant, including Klebsiella pneumoniae carbapenemase (KPC)-producing variants [3,5]. Interest has increased in gram-negative pathogens over recent years because they are associated with a higher mortality [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, patients treated in intensive care units (ICUs) with an MDR pathogen prevalence of >25% have an increased risk of developing MDR VAP, regardless of other risk factors [7][8][9]. For this reason, determining the frequency of MDR pathogens in ICUs is essential [3,5].…”
Section: Introductionmentioning
confidence: 99%
“…The role of metabolomics in this case is illustrated by the following examples. Streptococcus pneumoniae is the most frequent infectious agent across the whole spectrum of patients with CAP (outpatients, hospitalized, ICU) [85], whereas Staphylococcus aureus is, together with Pseudomonas aeruginosa , the most frequent isolate in cases of hospital-acquired pneumonia (HAP) in ICU [86]. Quantitative metabolomics with the use of NMR in urine samples of patients with CAP have revealed a distinct metabolic profile for pneumococcal pneumonia as compared to viruses and other bacterial agents [87].…”
Section: Metabolomics In Sepsismentioning
confidence: 99%